การสำรวจกิจกรรมของพระสงฆ์ในภาคคณะสงฆ์ 2 เกี่ยวกับการศึกษานอกระบบโรงเรียน - สุภา นวกรรมิก (จุฬาลงกรณ์มหาวิทยาลัย, 1986)
The purposes of this research were, first, to survey monks non-formal educational activities, second, to study and compare problems and obstacles in non-formal education operation, third, to study and compare opinions toward non-formal education of the monks with different backgrounds and fourth, to compare differences among temples sizes, types, incomes and location with non-formal education operation. The research samples, selected by stratified random sampling included 328 Wats in the Ecclesiastical Region 2. Research instruments were questionnaires developed by the researcher devided into 5 parts consisted of 1) samples personal information, temples general information and information about educational activities 2) monks participation in educational activities operated by the temples 3) relation study between monks personal information as well as temples general information with non-formal educational activity operation 4) the study of problems and obstacles in non-formal education operation and the study of opinions about non-formal education task 5) the comparative study of monks opinions in non-formal education operation. Data were analyzed by the Statistical Packages for the Social Sciences through the use of percentages, means standard deviation, chi-square, two – way analysis of variance. Differences between the pairs of groups were tested by the Scheffe s – Method. Findings : 1. The activities in non-formal education which the most temples had held were orderly Dhamma sermon on Wan Phra Days 84.5% ecclesiastical Dhamma study 73.8% special sermon on The Buddha s teaching 62.8%, community Dhamma training 57.9%, teaching morality in local schools 54.9%, insight meditation training 45.1% and the least, elementary and secondary education for adult 1.5% 2. Due to the monks participation in educational activities, the most monks were instructors and the others were the coordinators between temples and organizations. 3. Significant differences at .05 were found in comparison among different education activities of monks who had different ordination period and education level except the activities of vocational training and about education. 4. Significant differences at .05 were found in comparison among non-formal educational activities of temples which were different in size, type, income, location and being selected as the models of developed temples except the activities of 1) the ecclesiastical secondary schools 2) the adult education 3) Abhidhamma teaching 4) morality teaching for prisoners and 5) Dhamma teaching for prisoners. 5. Problems and obstacles in non-formal education operation which were at high levl were lacking of money for education operation lacking of man power and lacking of educational accessories. 6. Opinions about non-formal education operation were in highest agreement regarding that school teachers should have special knowledge such as ability in counseling and quidance in order to encourage students in studying. Almost all of the other opinions were at agreement level. 7. In comparison of opinions about problems and obstacles in non-formal education operation of monks who were different in ordination period and education level both in formal and in ecclesiastical Dhamma study, the results were 7.1 The monks who had long period of ordination thought that there were problems and obstacles in education operation at the high level in 1) lacking of money for education operation 2) lacking of man power 3) lacking of educational accessories but the monks with short ordination period regarded these problems and obstacles at the law level. 7.2 Significant differences at .05 were found in comparison among opinions of the monks with different education levels on lacking of man power in non-formal education operation 7.3 The monks who had high ecclesiastical Dhamma study though that then were problems and obstacles in education operation at the high level in 1) senior monks little cooperation and support 2) local people s little interest 3) unappropriate places for education and 4) student s different educational basic but the monks with the primary ecclesiastical Dhamma study regarded these problems and obstacles at the low level. 8. In comparison of opinions about non-formal education activities of monks who were different in ordination period and education level both in formal and in ecclesiastical Dhamma study, the results were 8.1 The monks with long period of ordination had high agreement regarding almost all educational activities but those with short period had the low agreement 8.2 The monks with secondary education had higher agreement in distributing knowledge of non formal educational activities to monks than those with the elementary education 8.3 The monks with high ecclesiastical Dhamma study agreed at the high level in the opinions that 1) in-town temples had more chances in developing educational activities than rural temples 2) non-formal and formal education had to be run in parallel. 3) governmental organization should allow monks to help in non-formal education operation. 4) education operation in temples had come from creative ideas the monks who had high education while those with primary ecclesiastical Dhamma study had only little agreement in it.